How to Overcome Obstacles to Improve Receptive Skills (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the difficulties that students studying a foreign language face when moving to more advanced levels, describes the features of these difficulties that will help teachers and, possibly, the students themselves, detect them in time. The article also suggests methods and techniques to prevent and overcome their negative impact on the learning process and to improve receptive skills.